Representation of social class and hierarchy in Bangla address terms: A Sociolinguistic Study - Snigdha, Shayla Sharmin (Journal of Modern Languages, 2022)
Address terms are important language components that represent the existing norms and practices of behaviour, holding specific contextual meanings in society and adding meanings beyond linguistic codes. This paper explores the connection of Bangla address terms with various parameters like age, religious identity, power position, social relationship, ratio of intimacy, and geo-spatial cultural variation through a close analysis of selected discourses. Based on these parameters, it is found that Bangla speakers use a wide range of address terms, which is a special feature of this language, in contrast to English or other languages. In Bangladeshi societies, kinship terms reflect the relationships among the addresser and the addressee, which vary based on paternal and maternal sides, and in different religious and cultural contexts. By employing a qualitative approach to explore the social interaction process, this paper sheds light on the use of Bangla address terms in a culturally diverse context from a sociolinguistic perspective.